2016
DOI: 10.1177/1077546315575835
|View full text |Cite
|
Sign up to set email alerts
|

Vibration response analysis of blade-disk dovetail structure under blade tip rubbing condition

Abstract: A cyclic sector corresponding to blade-disk structure with dovetail connection (1/38 blade-disk) is studied and the finite element (FE) model of this structure is established based on ANSYS software. A revised normal rubbing force model is developed and a pulse force model is established to simulate the local rubbing phenomenon between the blade and elastic casing based on the revised model. The effects of the rubbing under different rotating speeds and penetration depths on the blade vibration response and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 26 publications
0
32
0
2
Order By: Relevance
“…Using this phenomenological approach, a very long sequence of rubbing events may be simulated but the restriction of rubbing induced contact forces to a pulse load [2,3] fully known a priori filters contact related nonlinearities thus making it impossible to predict some potentially critical interaction phenomena. Additionally, when a pulse load is considered, strong assumptions are often made on the way the load is applied along the blade tip, simplified analytical models are also frequently used for the simulation of rubbing events [18,14,19]. In this case, contact conditions are typically treated by a penalty law: on one hand residual penetrations are tolerated and wear removal cannot be physically accounted for but on the other hand, sophisticated bifurcation analyses may be carried out under the assumption that interaction motions are periodic, and interesting qualitative results may be obtained in order to characterize the nature of interaction phenomena, a reduced-order model based [13,20,21] approach, which is used in this article, is the last known method to simulate rubbing events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this phenomenological approach, a very long sequence of rubbing events may be simulated but the restriction of rubbing induced contact forces to a pulse load [2,3] fully known a priori filters contact related nonlinearities thus making it impossible to predict some potentially critical interaction phenomena. Additionally, when a pulse load is considered, strong assumptions are often made on the way the load is applied along the blade tip, simplified analytical models are also frequently used for the simulation of rubbing events [18,14,19]. In this case, contact conditions are typically treated by a penalty law: on one hand residual penetrations are tolerated and wear removal cannot be physically accounted for but on the other hand, sophisticated bifurcation analyses may be carried out under the assumption that interaction motions are periodic, and interesting qualitative results may be obtained in order to characterize the nature of interaction phenomena, a reduced-order model based [13,20,21] approach, which is used in this article, is the last known method to simulate rubbing events.…”
Section: Introductionmentioning
confidence: 99%
“…For this experimental set-up, it is found that the witnessed interaction involves a single blade-thus it should be analysed as a sequence of rubbing events-, more specifically its first torsional mode, which is its second free-vibration mode. The numerical simulation of rubbing events has been the center of attention in a significant number of recent publications [2,12,13,14]. Several strategies may be employed to simulate such occurrences: a brute-force approach using a commercial finite element software with full 3D finite element models for the rotating components [15] is sometimes considered.…”
Section: Introductionmentioning
confidence: 99%
“…Different numerical strategies can be applied to the prediction of contact interactions: phenomenological approaches [5,6], analytical models [21,22], simplified models [6,23], finite elements through brute force modelling [24] or through a more efficient formulation with reduced order models [20]. Simulations can be carried out in the time domain [17,23] or in the frequency domain [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations can be carried out in the time domain [17,23] or in the frequency domain [25,26]. Contact is managed either with a penalty model [10], with Lagrange multipliers [27] or with the augmented Lagrangian approach [21]. Moreover, some models include the casing dynamics [28] or account for the removal of abradable coating [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such hypothesis is commonly accepted when investigating low-or high-pressure compressor stages. For that reason, numerical simulations of two types of rotor/stator interactions namely (1) rubbing phenomena [4,5,6] and, (2) modal interaction events [7,8] have been conducted without accounting for gyroscopic effects. A third type of rotor/stator interactions due to structural contacts is related to the occurence of orbital motions of an aircraft engine fan stage around its axis of rotation.…”
Section: Introductionmentioning
confidence: 99%